ANALISIS SWOT FINANCIAL TECHNOLOGY PADA DUNIA PERBANKAN DI KOTA AMBON (Survei Pada Bank di Kota Ambon) - Ferry Hendro Basuki; Hartina Husein (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
The purpose of this research is to analyze the swot fintech approach for bankingindustry in ambon city. There are 8 banks as the subject of informants used inanalyzing the fintech SWOT application from the banking industry side offintech kalobarasi from the bank industry is the solution to the presence offintech. Through the collaboration will enslave and maximize banking servicesin the city of ambon.